Analyzing Coaches’ Skills: A Survey of Table Tennis Coaches in Riau Province and DIY Province, Indonesia - Ali Mandan; Syahriadi; Trisnar Adi Prabowo (Indonesian Journal of Physical Education and Sport Science, 2024)
Studi purpose. The purpose of this study was to determine the ideal coach skills for Table Tennis. Materials and methods. This research was descriptive and quantitative using a survey. The sample of this study were athletes who had won medals in table tennis competitions at the city or district level in Riau Province and Yogyakarta Special Region (DIY) Province as evidenced by certificates during 2023. Therefore, the sample of table tennis athletes involved was 70 athletes (44 boys and 26 girls). The characteristics of the athletes were an average age of 18.7±7.2 years and 6.1±0.9 years of training experience. The research instrument was a questionnaire distributed via a Google form. The questionnaire contained 20 statement items with a scale of 1 - 4. The coach’s skills are divided into 4 factors (table 1), which were 1) skills in applying sports techniques, 2) skills in applying training periodization, 3) psychological skills, and 4) communication skills. Results. Table Tennis Coaches’ skills in general showed "very poor" 2 answers (3.32%), "poor" 19 answers (28.33%), "fair" 25 answers (33.53%), "good" 22 answers (31.68%), and "very good" 2 answers (3.32%). Conclusions. From the results of this study, it is expected that the Riau Province and DIY Province table tennis organizations pay more attention to the quality of coach skills. One effective solution at this time is to provide training to coaches in stages. Further, providing opportunities for former athletes who no longer have a career to be given basic coaching knowledge so that later they can become professional coaches.